Practical Leadership: Learning from Great Rulers in History - Jennifer H. Operio (Journal of Social Entrepreneurship Theory and Practice, 2021)
This paper examines the applied principles and leadership styles of great ancient men in the light of the Bible as the Word of God. Practically speaking, scholarly literature in leadership and management lacked attention to the study of biblical figures as leaders. The author utilised secondary analysis of qualitative information from documented life stories of renowned leaders in human history. This paper utilizes qualitative content analysis to evaluate patterns of popular ancient leaders' styles in leading their subjects. With content analysis, the author is obliged to read and re-read the text, specifically the Bible, as the main source of data and focus on the specific timeline of the ancient world. The scope and limitation of this paper cover only the discussion on the prominent historical people, specifically Biblical characters, and does not include the current leaders of our time. This paper hopes to bring back the basics on leading people worth emulating by modern-day leaders. It explores the successes and failures of these ancient leaders that shaped history and even world cultures. It also aims to promote a blueprint that was already utilised by leaders in the ancient world regarding leading constituents and subjects. The scope and limitation of this study enfold the discussion on the prominent historical people and does not include the current leaders of our modern time.